Nanoscale compositional modification in Co/Pd multilayers for controllable domain wall pinning in racetrack memory - Jin, Tianli (2020)
In the era of social media, storage of information plays an important role. Magnetic domain wall memory devices are promising alternatives to hard disk drives for high‐capacity storage. One of the challenges in making these devices for practical application is a precise control of domain wall displacement in nanowires. Researchers have extensively studied domain wall pinning based on topographical notches fabricated by lithography. However, scaling the domain wall memory to nanoscale requires better domain wall pinning strategies. In this letter, we demonstrate that the localized modification of magnetic properties in Co/Pd multilayer‐based nanowires by ion implantation is an effective non‐topographical approach to pin domain walls. First, by micromagnetic simulations, it is shown that the areas, where the composition is modified to tune the anisotropy and magnetization, act as domain wall pinning centers. Experimentally, from magnetization measurements and X‐ray diffraction measurements at the thin film level, it is shown that the ion‐implantation is effective in changing magnetic anisotropy. Devices have also been fabricated and, using Kerr images at different applied fields, it is shown that the domain walls are pinned at the B+ ion‐implanted regions. These results demonstrate that localized compositional modification using ion‐implantation can pin domain walls precisely. The achieved results are useful toward realizing high‐capacity information storage.